Technology and Organizations/Organizations and Communication TechnologyTechnology and Organizations, by Goodman Paul S. Sproull Lee S., and Associates. San Francisco: Jossey-Bass, 1990, 281 pp., $27.95, cloth.Organizations and Communication Technology, edited by Fulk Janet Steinfield Charles. Newbury Park, CA: Sage Publications, 1990, 328 pp., $18.95, paper; $38.00, cloth. - Jelinek, Mariann (Academy of Management Review, 1991)
This article presents a review of two books, “Technology and Organizations,” by Paul S. Goodman and Lee S. Sproull and “Organizations and Communication Technology,” edited by Janet Fulk and Charles Steinfield.